Development of metal hydride systems for thermal energy storage applications - Poupin, Lucas Michel Dominique (Curtin University, 2020)
This thesis project furthers the development of innovative high temperature thermal energy storage using metal hydrides. The research greatly enhances the gravimetric energy density, which has the potential to lead to an increased efficiency of thermal energy storage. The project aimed at selecting suitable metal hydrides for scaling up and the investigation of heat storing reactors. Three systems were studied, including an autonomously operating thermal energy store of 1.8 MJ at 450 °C.